A Smart Superwetting Surface with Responsivity in Both Surface Chemistry and Microstructure. (28th February 2018) - Zhang, Dongjie; Cheng, Zhongjun; Kang, Hongjun; Yu, Jianxin; Liu, Yuyan; Jiang, Lei
Abstract: Recently, smart surfaces with switchable wettability have aroused much attention. However, only single surface chemistry or the microstructure can be changed on these surfaces, which significantly limits their wetting performances, controllability, and applications. A new surface with both tunable surface microstructure and chemistry was prepared by grafting poly(N‐isopropylacrylamide) onto the pillar‐structured shape memory polymer on which multiple wetting states from superhydrophilicity to superhydrophobicity can be reversibly and precisely controlled by synergistically regulating the surface microstructure and chemistry. Meanwhile, based on the excellent controllability, we also showed the application of the surface as a rewritable platform, and various gradient wettings can be obtained. This work presents for the first time a surface with controllability in both surface chemistry and microstructure, which starts some new ideas for the design of novel superwetting materials.